Land of Hope: British Colonization in New Zealand (1840-1855) - Ipong Jazimah; Arifin Suryo Nugroho; Rendi Marta Agung; Syifa Nur Tsaltsa Amalia (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
New Zealand was initially a refuge for British convicts from Australia and was regarded as a land of hope for rebuilding their lives. Over time, however, New Zealand was inhabited not only by convicts but also by various other groups seeking economic opportunity and a new livelihood. This development prompted the British government to establish a colonial state in New Zealand in 1840, appointing William Hobson as its first governor. This study aims to examine British colonization in New Zealand, encompassing the Treaty of Waitangi and the early formation of the colony, New Zealand’s transformation into a British crown colony, and the situation in New Zealand between 1852 and 1855. The research employs the historical method, which consists of several stages: topic selection, source collection (utilizing heuristics), verification (external and internal criticism), interpretation (analysis and synthesis), and historiography. The findings suggest that the need for territorial expansion and competition with France contributed to the establishment of a British colonial state in New Zealand. The colony of New Zealand was formally established through the Treaty of Waitangi, signed by British representatives and Maori chiefs. In 1841, New Zealand officially became a crown colony, meaning that it possessed a structured system of colonial governance under a governor with authority comparable to that of other British colonies worldwide. During the period 1852–1855, New Zealand experienced numerous conflicts over land disputes between European settlers (pakeha) and the Maori.